DIFFERENCE OF VITAMIN C CONTENT IN PICKLED MANGO FRUIT - Sri Palupi (Jurnal Penelitian Saintek, 2003)
his research is a survey one which aims at knowing the content of vitamin C of salted mangoes and knowing existances or non-extances of the content of vitamin C of salted mangoes in Jogjakarta Special Region (DIY). Knowing existances or nonextances of the differences of the content of vitamin C of salted mangoes the supply of vitamin C will -be known so  that the  need  of vitamin  C for  someone  can  be considered as references.  The samples  are salted  mangoes sold  at Mirota Kampus, Gardena and Ramai shop. These shops only sell them every  sample  was  analyzed  to find   out  its  water  and  vitamin  C contents using "titrasi yodium"  with four  time repetitions. These data then was analyzed statistically using two ways of variant analysis. The summary of this research shows that the content of vitamin C every lOO-grama salted mango driedfrom  Mirota Kampus has 0,141 gram, Gardena has 0,094 gram. There significant differences of the content of vitamin C of the salted mangoes from the 3 shops. A Null hypothesis (Ho) accepts, p    0,05. It is  suggested  that people  buys the salted mangoes  at Mirota Kampus shop  because  its vitamin  C content is higher.